2021
DOI: 10.26555/humanitas.v18i2.19027
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and academic resilience among unprivileged college students: The mediating role of self-compassion

Abstract: A growing body of studies shows that the higher individuals' education level, the higher their chance of getting a better salary. Unfortunately, for unprivileged students who want to improve their living conditions, the risk of failure to complete college is much higher because of numerous obstacles regarding their economic status. Having good academic resilience may foster unprivileged college students to achieve success in their studies. This study aimed to find out the relationship between mindfulness and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Kuala students. There was positive correlation between mindfulness and academic resilience in students which is supported by literature, including research, which stated that mindfulness had a significantly positive correlation with academic resilience (Sari & Munawaroh, 2022), Riaz, 2018), and(Liu et al, 2020. In line with this, Salsabila & Widyasari (2021) revealed that mindfulness contributes to a better ability to face challenges, achieve college success, or increase academic resilience. Mindfulness directly influenced and increased academic resilience (MacArthur et al, 2017;Olson & Emery, 2015).…”
Section: This Research Was Undertaken To Determine Correlation Betwee...mentioning
confidence: 54%
“…Kuala students. There was positive correlation between mindfulness and academic resilience in students which is supported by literature, including research, which stated that mindfulness had a significantly positive correlation with academic resilience (Sari & Munawaroh, 2022), Riaz, 2018), and(Liu et al, 2020. In line with this, Salsabila & Widyasari (2021) revealed that mindfulness contributes to a better ability to face challenges, achieve college success, or increase academic resilience. Mindfulness directly influenced and increased academic resilience (MacArthur et al, 2017;Olson & Emery, 2015).…”
Section: This Research Was Undertaken To Determine Correlation Betwee...mentioning
confidence: 54%
“…The analysis focused on research conducted on Indonesian participants. The results of the analysis obtained by the researcher are described in the following table: Several research articles analyzed illustrate that self-compassion correlates with several psychological variables including loneliness and depression (Ausie & Poerwandari, 2021), mindfulness and depression (Fourianalistyawati et al, 2018), mindfulness and resilience (Salsabila & Widyasari, 2021), mental well-being and Irani Harefa, Edi Hamdi, Tantri Yanuar, Rina Annindita academic engagement (Kotera et al, 2022), and self-regulation (Sugianto, Anna, & Sutanto, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Through this process, people have a greater capability to respond adaptively and skillfully to the stressor 20 , 21 , e.g., to generate compassion rather than criticisms towards the self and the others, which is further linked to a greater meaning in life. Supporting the basis of mindfulness-to-meaning theory 20 , previous research indicated that self-compassion mediated the relation between dispositional mindfulness and a myriad of psychological outcomes, including better psychological well-being among meditators and non-meditators 12 , 22 , greater academic resilience among underprivileged university students 23 , and lower severity of social anxiety among individuals with social anxiety disorder 24 .…”
Section: Introductionmentioning
confidence: 89%